PENGARUH REKRUTMEN, KOMPETENSI DAN BUDAYA ORGANISASI TERHADAP KINERJA KARYAWAN PT. LAUTAN BERLIAN UTAMA MOTOR CABANG LAHAT - Sudarta Sudarta; Zaleha Trihandayani; Amanda Suhadi (Gapenas Publisher, 2022)
The formulation of the problem in this study is whether there is a competency recruitment director and Badays, Organization on the performance of employees of PT. Lautan Berhan Utama Motor Lahat Branch. The research used in this study is associative. The population used in this study was 48 employees of and the sample used was taken in this study as many as 43 respondents. Yong method used in this research is qualitative and quantitative. The data collection technique is a questionnaire (Questionnaire). The analysis technique used in this study is multiple linear regression analysis such as hypothesis testing. The result of this study indicate that there is a significant influence between recruitment, competen and organizational culture on the performance of PT.Lautan Berlian Utama Motor Lahat Branch